Analisis Kesiapan Kontraktor Kecil Dalam Menghadapi Pelaksanaan Pekerjaan Proyek Pemerintah Di Kabupaten Ende - Yodaker, Yohanes Berkhemans; Meo, Yohanes; Radja, Veronika Miana (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
The government is trying to eliminate complaints from the tender system that has been implemented so far, of course, to bring equality and accelerate budget absorption so that development can run smoothly and the welfare of the community is realized. To implement the principles of Good Governance and Clean Government, the government must be ready to implement the principles of accountability, resources, finance, technology, and innovation, and complete qualifications, efficiently and implement good and impartial actions and regulations, as well as ensure interaction economic and social relations between the government. The research method consists of literature study, determination of research object, data collection by using questionnaires and interviews, and data analysis. The object of this research is a small-scale contractor in Ende Regency, under the auspices of APAKSINDO (Association of Indonesian Construction Entrepreneurs) Ende branch. The method of data collection was done by questionnaire to the contractor. Data from the questionnaire was then analyzed including validity test and linear regression analysis and T-test analysis. The results of this study indicate the level of readiness of contractors in the Ende Regency, some state that they are ready for all the regulations given by the Ende Regency Construction Services and some state that they are not ready. The more dominant readiness factors include the readiness of resources, finance, technology and innovation, and qualifications that affect the level of contractor readiness.